2017
DOI: 10.1038/s41598-017-10879-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cholesterol homeostasis in lung diseases

Abstract: Macrophages are critical to organ structure and function in health and disease. To determine mechanisms by which granulocyte/macrophage-colony stimulating factor (GM-CSF) signaling normally maintains surfactant homeostasis and how its disruption causes pulmonary alveolar proteinosis (PAP), we evaluated lipid composition in alveolar macrophages and lung surfactant, macrophage-mediated surfactant clearance kinetics/dynamics, and cholesterol-targeted pharmacotherapy of PAP in vitro and in vivo. Without GM-CSF sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 61 publications
8
73
0
Order By: Relevance
“…This functional response is characterized by the cells being predominantly cholesterol-laden. In pulmonary alveolar proteinosis, increased cholesterol/lipid accumulation within AMs might be mediated by defective GM-CSF signaling and, as a consequence, reduced PPARG and cholesterol transporter (ABCG1) expression (De Aguiar Vallim et al, 2017;Sallese et al, 2017;Trapnell et al, 2019). This mechanism is unlikely in COPD since we do not observe clear downregulation of either PPARG ( Figure S3F) or ABCG1 ( Figure 3D).…”
Section: Altered Lipid Metabolism In Ams Of Copd Patientsmentioning
confidence: 83%
See 1 more Smart Citation
“…This functional response is characterized by the cells being predominantly cholesterol-laden. In pulmonary alveolar proteinosis, increased cholesterol/lipid accumulation within AMs might be mediated by defective GM-CSF signaling and, as a consequence, reduced PPARG and cholesterol transporter (ABCG1) expression (De Aguiar Vallim et al, 2017;Sallese et al, 2017;Trapnell et al, 2019). This mechanism is unlikely in COPD since we do not observe clear downregulation of either PPARG ( Figure S3F) or ABCG1 ( Figure 3D).…”
Section: Altered Lipid Metabolism In Ams Of Copd Patientsmentioning
confidence: 83%
“…Thus, they are highly associated with lipid metabolism. Failure of this 'accessory' function is reflected by pulmonary alveolar proteinosis (PAP), in which defective GM-CSF signaling in AMs causes an accumulation of surfactant-derived lipids in AMs and the AS (De Aguiar Vallim et al, 2017;Sallese et al, 2017;Trapnell et al, 2019). However, due to the expression of ABCG1 in AMs from COPD patients, the accumulation of cholesteryl ester must be due to alternative molecular mechanisms than in PAP (De Aguiar Vallim et al, 2017;Baker et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these other roles, GM-CSF gene-deficient mice showed minimal changes in steady state myelopoiesis but developed pulmonary alveolar proteinosis (PAP) as the major phenotype indicating GM-CSF involvement in lung surfactant homeostasis (Dranoff et al, 1994;Stanley et al, 1994); this finding indicated a role for GM-CSF in alveolar macrophage development, which has been found to be dependent on the transcription factor PPARγ (Schneider et al, 2014). It has been proposed recently that GM-CSF is required for cholesterol clearance in alveolar macrophages, with a reduction in this clearance being the primary macrophage defect driving PAP (Sallese et al, 2017;Trapnell et al, 2019). This lung data suggest a fundamental role for GM-CSF in lipid (cholesterol) metabolism consistent with a proposed protective role in atherosclerosis (Ditiatkovski et al, 2006;see below).…”
Section: Introductionmentioning
confidence: 96%
“…Decreased cholesterol clearance leads to the foamy appearance of macrophages and is conceivably the rate limiting step of macrophage dysfunction in PAP. 106,107 Reduced GM-CSF signaling (either due to autoantibodies or receptor dysfunction) results in reduced (peroxisome proliferator-activated receptor gamma) PPARγ gene expression in macrophages of primary PAP. In turn this results in lower expression of the cell surface cholesterol transporters ABCG1 and ABCA1.…”
Section: Targeting Macrophage Cholesterol Homeostasismentioning
confidence: 99%